Odroczenie kary pozbawienia wolności wobec kobiet - Mrozek, Kamila; Sitnik, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Enforcement of custodial sentences with regard to women is a peculiar problem of penitentiary nature, determined by biological and psychological gender-related determinants. That is why the implementing penal measures regulated differently for this group of inmates include deferment of custodial sentences. Deferment of custodial sentences constitutes an exception to the principle of immediate enforcement.
Keywords: kara pozbawienia wolności; odroczenie wyroku; skazana kobieta